2021
DOI: 10.5267/j.ac.2020.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Financial development and poverty reduction in developing countries

Abstract: The poverty becomes a serious problem because of the impact it causes. The factors that affect poverty are economic growth, low education, the limitation of natural resources, the limitation of employment opportunities, capital, and family burdens. All of these factors constitute a vicious circle in the problem of poverty. The problems studied are lag-1 investment, lag-2 investment, employment opportunities, and provincial minimum wages and their effects on the poverty rates in Riau Province, Indonesia. The fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…As this happens, living standards increase, reflecting positively in their poverty reduction levels. This finding supports that of Zulher and Ratnasih (2021), Zhang et al (2021), and Krishna (2020), who found that local employment creation leads to poverty reduction. Nonetheless, this finding refutes that of Ravallion (2019) and Osabohien et al (2020), who found that local employment creation does not have a positive link with poverty reduction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As this happens, living standards increase, reflecting positively in their poverty reduction levels. This finding supports that of Zulher and Ratnasih (2021), Zhang et al (2021), and Krishna (2020), who found that local employment creation leads to poverty reduction. Nonetheless, this finding refutes that of Ravallion (2019) and Osabohien et al (2020), who found that local employment creation does not have a positive link with poverty reduction.…”
Section: Discussionsupporting
confidence: 90%
“…Another factor that can influence poverty reduction is the creation of local employment avenues. To delve deeper, Zulher and Ratnasih (2021) revealed that employment creation by the local government affects poverty reduction in Indonesia. Zhang et al (2021) wrote that the irrigation schemes initiated through the support of the local government created jobs for community members and again increased their financial gains, thereby reducing their poverty levels to minimum levels in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of the two sectors base on the surplus of labour generated from the agricultural sector. The existence of change or transition as a characteristic of development is also stated by Zulher C. Ratnasih [1], who defines economic development as a multidimensional process that includes changes in structure, life attitudes, and institutions, apart from increasing economic growth, reducing distribution inequality and poverty eradication. From an employment perspective, Srinivasan [2] argues that development expresses as a transfer of labour from agriculture to industry and services.…”
Section: Theorymentioning
confidence: 95%
“…Where Human Resources is one thing that cannot be separated from the level of the business world and work and especially now that there is a lot of competition in the business world. The role of motivation, environment and work experience which will later become one important role of work encouragement for the employee himself (Zulher & Ratnasih, 2021).…”
Section: Althoughmentioning
confidence: 99%